Table 4_Insights into Mycobacterium abscessus survival under prolonged potassium deficiency and starvation.xlsx - Artem S. Grigorov (7056344) (2025)
Mycobacterium abscessus (Mab) is known for its ability to cause chronic infections, to be resistant to antimicrobial agents and to survive for extended periods in different non-replicative states (NRS), including persistence, dormancy or starvation. Functional metabolic pathways for Mab surviving in particular NRS caused by potassium depletion or by starvation, which are the conditions common in infected hosts or natural environments, remains unexplored. Dormant and starved Mab cultures were able to maintain viability, exhibiting decreased 3H‐uracil incorporation and altered cell ultrastructure compared to actively growing cells. Specifically, dormant Mab populations were heterogeneous in the ability to cope with potassium deficiency, either maintaining very low or near-normal K+-levels, or capturing other cations. Transcriptome and proteome profiling revealed both common and specific metabolic reprogramming in dormant and starved Mab, including downregulation of the major biosynthetic pathways and upregulation of β-oxidation of fatty acid. Specifically, dormant Mab cells were enriched in the dormancy regulator DosR and the potassium-transporting Kdp system, corresponding to their enhanced transcription. Unlike dormant Mab, starved Mab contained an elevated pool of proteins underrepresented in transcriptome, such as the DNA-binding histone-like protein and the universal stress proteins. In dormant Mab, up- or down-regulation at the transcriptional and translational level matches better than in starved cells. Notably, transcripts and proteins of the MmpL and MmpS family, which are associated with mycobacterial virulence, and lipid-transporting Mce proteins, which modulate host-cell signaling, were depleted in the both dormant and starved Mab. Overall, the results of this study provide insight into molecular mechanisms by which Mab adapts to clinically relevant and long-term environmental stresses and survives in NRS.